Evaluation of the coordinated development of health resources, health service utilization, and the regional economy in China and analysis of influencing factors - Lina Shao; Zhonghua Suo; Shasha Song; Ying Lang (BMC Health Services Research)
Abstract Objective This study investigates the coupling coordination relationships and influencing factors of health resources, health service utilization, and regional economy in China, aiming to provide reasonable suggestions for promoting the coordinated development of medical and health services and regional economy. Methods The panel data from 2016 to 2021 on China’s health resources, health service utilization were analyzed concerning China’s health resources, health service utilization, and regional economy. These included the entropy weight method for index weight calculation, the synthesis level index for subsystem synthesis level calculation, a coupled coordinated development model, exploratory spatial data analysis, and a geographic detector model. These analytical approaches facilitated the examination of spatial and temporal variances, alongside the identification of driving factors influencing the coupled and coordinated development of health resources, health service utilization, and regional economy in China. Results The findings reveal that (1) a high level of coupling exists among the three subsystems across all provinces in China. (2) Concerning the spatial pattern of coupling coordination, notable regional differences are observed in the degree of coupling coordination between health resource utilization, health service utilization, and regional economic development, with a noticeable decline from east to west and central regions positioned in between. (3) Regarding spatial evolution characteristics, an overall trend of higher levels is observed in the east and north compared to the west and south, indicating localized spatial clustering. In the south‒north direction, there is a parabolic rise followed by a decline from north to south. In the east‒west direction, there is an inverted “U” shaped curve with gradual strengthening from east to west. (4) The spatial disparities in synergetic development among health resource utilization, health service utilization, and the regional economy arise from multiple influencing factors interacting with each other. (5) Spatial variations are noted in the impacts of driving factors on coordinated development among health resource utilization, health service utilization, and the regional economy during different time periods. Conclusion Regional disparities primarily arise from various factors, such as healthcare visit frequency, healthcare human resource availability, and healthcare material resource allocation; moreover, these factors also vary geographically across different time periods. Strategic measures for medical care services and economic development should be formulated by each region based on its own circumstances to enhance economic benefits and achieve coordinated high-quality development among health resource utilization, health service utilization, and the regional economy.